2008
DOI: 10.1002/app.28071
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of fumed silica/cyanate ester nanocomposites

Abstract: ABSTRACT:The thermal expansion behavior of a cyanate ester matrix reinforced by fumed silica nanoparticles with average primary particle diameters of 12 and 40 nm was investigated with thermomechanical analysis. All nanocomposites showed decreased coefficients of thermal expansion (CTEs) in comparison with the neat bisphenol E cyanate ester resin, but the 12-nm fumed silica nanocomposites had lower CTEs than the 40-nm nanocomposites for equal volume fractions. The largest decrease in CTE was 27.0% for 20.7 vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 32 publications
(56 reference statements)
1
25
0
Order By: Relevance
“…Sun et al [13] compared the dimensional stabilities of micro-and nano-silica-reinforced epoxy composites and demonstrated that the nanofillers could decrease the coefficient of thermal expansion (CTE) of a base polymer better than micron-sized fillers. Goertzen and Kessler [14] reported the same experimental result for the CTE of nanosilica/cyanate ester nanocomposites. More recently, using the same silica/epoxy composites, Jang et al [15] reported a clear filler size effect in the http://dx.doi.org/10.1016/j.compstruct.2015.03.041 0263-8223/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionsupporting
confidence: 70%
“…Sun et al [13] compared the dimensional stabilities of micro-and nano-silica-reinforced epoxy composites and demonstrated that the nanofillers could decrease the coefficient of thermal expansion (CTE) of a base polymer better than micron-sized fillers. Goertzen and Kessler [14] reported the same experimental result for the CTE of nanosilica/cyanate ester nanocomposites. More recently, using the same silica/epoxy composites, Jang et al [15] reported a clear filler size effect in the http://dx.doi.org/10.1016/j.compstruct.2015.03.041 0263-8223/Ó 2015 Elsevier Ltd. All rights reserved.…”
Section: Introductionsupporting
confidence: 70%
“…Typically, the three models that are used to predict CTE for polymer/filler composites are the rule of mixtures, Turner's model, and Schapery's model. 13,25,26 The rule of mixtures involves computing the CTE of the composite based on the CTE of the filler (a f ), the CTE of the polymer matrix (a m ), and the filler volume fraction (j f ), as shown in Eq. (1) below:…”
Section: Resultsmentioning
confidence: 99%
“…12), including silica [54,55], alumina [54], aluminum nitride (SCAN) [54], nanoclay [12,56] and POSS [10]. The CTEs reported in Fig.…”
Section: Coefficient Of Thermal Expansion (Cte)mentioning
confidence: 96%